DATA SECURITY STRATEGY BASED ON STORED PROGRAMS: A CASE STUDY OF DSS FOR TEACHING ASSISTANT SELECTION - Prahenusa Wahyu Ciptadi; Tri Hastono; Gema Kharismajati; Firdiyan Syah; Nayaka Anung Fahriza (JTH: Journal of Technology and Health, 2025)
Data security is increasingly crucial in managing information systems, especially in academic environments handling sensitive data. The reliance on digital systems demands protection of data integrity, confidentiality, and availability. Educational institutions must secure student, faculty, and administrative data to prevent unauthorized access and manipulation. One system requiring high security is the Decision Support System (DSS) for Teaching Assistant selection. DSS helps determine candidates based on GPA, experience, and skills. However, it is vulnerable to unauthorized data changes, access abuse, SQL Injection, and cyber threats that may affect decision accuracy. Stored Programs in databases provide an effective solution for enhancing data security. With Stored Procedures, Functions, Triggers, and Events, data management becomes more secure and structured. These features enable stricter access control, database operation automation, and direct validation to reduce errors and misuse. In the DSS case study, Stored Programs ensure that only authorized users can access and modify data. Authentication and authorization mechanisms restrict access based on user roles. This study analyzes security risks, system architecture design, Stored Program implementation, and its effectiveness in maintaining data integrity. Research results confirm that the developed Stored Programs meet expectations. The CRUD feature operates optimally with a processing time of 0.0059 seconds.